Designing a B Cell-Based Vaccine against a Highly Variable Hepatitis C Virus - Fuerst, Thomas R.; Pierce, Brian G.; Keck, Zhen-Yong; Foung, Steven K. H. (Frontiers in Microbiology, 2018)
The ability to use structure-based design and engineering to control the molecular shape and reactivity of an immunogen to induce protective responses shows great promise, along with corresponding advancements in vaccine testing and evaluation systems. We describe in this review new paradigms for the development of a B cell based HCV vaccine. Advances in test systems to measure in vitro and in vivo antibody-mediated virus neutralization include retroviral pseudotype particles expressing HCV E1E2 glycoproteins (HCVpp), infectious cell culture-derived HCV virions (HCVcc), and surrogate animal models mimicking acute HCV infection. Their applications have established the role of broadly neutralizing antibodies to control HCV infection. However, the virus has immunogenic regions in the viral envelope glycoproteins that are associated with viral escape or non-neutralizing antibodies. These regions serve as immunologic decoys that divert the antibody response from less prominent conserved regions mediating virus neutralization. This review outlines the immunogenic regions on E2, which are roughly segregated into the hypervariable region 1 (HVR1), and five clusters of overlapping epitopes designated as antigenic domains A-E. Understanding the molecular architecture of conserved neutralizing epitopes within these antigenic domains, and how other antigenic regions or decoys deflect the immune response from these conserved regions will provide a roadmap for the rational design of an HCV vaccine.